Measurement of the W+W- cross section in √s=7TeV pp collisions with ATLAS - Anduaga, Xabier Sebastián (2011)
This Letter presents a measurement of the W+W- production cross section in √s=7TeV pp collisions by the ATLAS experiment, using 34pb-1 of integrated luminosity produced by the Large Hadron Collider at CERN. Selecting events with two isolated leptons, each either an electron or a muon, 8 candidate events are observed with an expected background of 1.7±0.6 events. The measured cross section is 41-16+20(stat) ±5(syst)±1(lumi)pb, which is consistent with the standard model prediction of 44±3pb calculated at next-to-leading order in QCD.